Tell me where you are: : strategies for permanence and success in emergency remote education at Instituto Federal de Educação, Ciência e Tecnologia da Bahia, Campus Simões Filho - Santana, Azly Santos Amorim de; Silva, Cláudia Cunha Torres da; Silva, Ivo Falcão da (Revista Labor, 2021)
This paper presents an account of experiences about the transition process from the in-person to the remote context at the Federal Institute of Education, Science and Technology of Bahia, campus of Simões Filho, in the face of the COVID-19 pandemic. The report is divided into three main parts, emphasizing the use of the chronological criterion of the facts narrated/analyzed. Initially, we discussed the main challenges encountered with the outbreak of the pandemic in the state of Bahia and the necessary actions to interrupt academic activities on campus. Then, we discuss the strategies that were used to find/group students in the integrated, subsequent and higher forms of our teaching unit. Finally, we explain about the actions taken with students during this period and how they had a positive impact on the process of permanence and combating school dropout.